Evaluation of antileishmanial potential of Gentiana kurroo Royle by in vitro and in silico methods - Sá, Laisa Lis Fontinelea de (2018)
Mucoadhesive tablets for administration in buccal mucosa are unconventional formulations with many technological attractions. However there is no standardization of information for its formulation. The present article aims to evaluate, by means of a systematic review with meta-analysis, the data related to the final quality of this technology. The development of oral tablets with 100 to 150 mg, including soluble drugs and sustained release for 6 hours or more, is a consensus. The most frequent polymers used are those derived from cellulose, Carbopol (CBM), Chitosan (CS), and Gums, alone or blended, with adhesive strength in the order: CBM > Alginates > cellulose derivatives > Gums. Among other results, this article demonstrates that this technology depends on a detailed analysis between the polymer, the physical characteristics of the tablet, the physicochemical characteristics of the drug to be incorporated and the buccal region in which it will remain in contact.